Approval procedures for large-scale renewable energy installations: Comparison of national legal frameworks in Japan, New Zealand, the EU and the US. (June 2019) - Schumacher, Kim
Abstract: This paper analyses the commonalities and variances of environmental approval procedures in four OECD territories, Japan, New Zealand (NZ), the European Union (EU), and the United States (US). In order to streamline regulatory approval frameworks for large-scale renewable energy (LS-RE) installations, outlining the strengths, as well as the weaknesses of the current systems in place, is crucial in determining what components to alter in line with national and regional particularities. The jurisdictional juxtaposition facilitates the identification of administrative burdens, which could increase environmental review-related costs for developers and prolong the entire approval process. Environmental impact assessment (EIA) frameworks, a major component of the LS-RE approval process, suffer from administrative fracturing between the local, regional, and national levels as well as between various government agencies. In combination with strong reservations from local civil society stakeholders, the results revealed some of the flaws of the current LS-RE project approval systems in place. The EIA frameworks and reform efforts in all four jurisdictions illustrate the importance of consolidated and comprehensive frameworks to reduce the amount of planning uncertainties for developers. Utilising regulatory tools such as mandatory timeframes, scoping, clear screening thresholds and priority assessment categories for LS-RE projects, could result in robust EIA processes based on unified regulatory procedures for climate change mitigating energy projects, inside as well as outside of OECD jurisdictions. Highlights: Review of large-scale renewable energy project approval procedures. Analysis of frameworks in Japan, New Zealand, the EU, and the US. Approval procedures can act as strong barriers to renewable energy development. Streamlining efforts in New Zealand and the EU facilitate procedures. Procedural reforms provide an additional balance between stakeholder interests.